Information Security using GNU Privacy Guard - Syed, Dabeeruddin; Al-Ghushami, Abdullah Hussein; Zainab, Ameema; Abdulhamid, Shafii Muhammad; Al-Kuwari, Mohammed Salem Daen A (2023 IEEE 13th Annual Computing and Communication Workshop and Conference (CCWC), 2023)
The CIA trinity of data system confidentiality, integrity, and availability is significantly reliant on communication networks in today's society. A major portion of the vital communication system infrastructure is dependent on huge, sophisticated software systems that may have defects and pose security threats. Data security has always been a primary issue, both online and offline. Several email, data, and communication systems are usually several years old and must be upgraded on a regular basis to keep possible hazards at bay. As a result, there is a pressing need to protect communication networks, internet data, and email systems from external threats. An overview of the GNU Privacy Guard (GNUPG) in the era of information security is presented in this paper. The paper also investigates the possibility and requirement of data transmission security. There is a description of various types of cryptography algorithms, mathematics, and science used in various asymmetric key algorithms. Furthermore, the GNUPG applications in several fields of keys and certificates are evaluated.